Performa Itik yang diberI Pakan Silase lImbah Sayuran Pasar (The Ducks Performance fed by Silage Vegetable Waste) - S. Herijanto; . Supranoto; E. Tugiyanti (Jurnal Ilmu dan Teknologi Peternakan, 2017)
Duck is monogastric that have higher ability to digest cellulose than other fowl, so there is a possibility that vegetable waste, which high fber content, can be used as feed. The objective of the research was to evaluate the performance of male duck fed by vegetable waste silage. The materials used were 75 male ducks of 3 to 4 week old (average body weight of 275-336g). The study was carried out according to completely randomized design, which consisted of fve treatments and three replications. The treatments were control, dried vegetable, vegetable waste fermentated with Lactobacillus casei, vegetable waste fermentatied with 20% cassava and 20% rice bran, and vegetable preserved with KMnO4, there were fve ducks in each experimental unit. Male ducks werefed on 16% protein and 2,900 ME kcal/kg with vegetable waste as much 20% for 13 weeks. Results showed that the use of vegetable waste in the ration signifcantly affected the body weight but had no effects on carcass percentage, liver percentage, and blood cholesterol. The highest ducks body weight 1,243.9 ± 33.4 g fed with vegetable waste fermentation with Lactobacillus casei, the best carcass percentage 64.85 ± 1.09% fed with dried vegetable, the highest liver percentage 2.6 ± 0.3% fed with 20% cassava and 20% rice bran, and the lowest blood cholesterol 137.04 ± 27.96mg/dl fed with vegetable preserved with KMnO4 . In conclusion, male duck fed with vegetable waste